Antifungal Saponins from the Maya Medicinal Plant Cestrum schlechtendahlii G. Don (Solanaceae). (15th December 2015) - Ta, Chieu Anh Kim; Guerrero‐Analco, J. Antonio; Roberts, Elizabeth; Liu, Rui; Mogg, Christopher D.; Saleem, Ammar; Otárola‐Rojas, Marco; Poveda, Luis; Sanchez‐Vindas, Pablo; Cal, Victor; Caal, Federico; Subramaniam, Rajagopal; et al.
Abstract : Bioassay‐guided fractionation of the crude extract (80% EtOH) of the leaves of Cestrum schlechtendahlii, a plant used by Q'eqchi' Maya healers for treatment of athlete's foot, resulted in the isolation and identification of two spirostanol saponins (1 and 2). Structure elucidation by MS, 1D‐NMR, and 2D‐NMR spectroscopic methods identified them to be the known saponin (25 R )‐1β, 2α‐dihydroxy‐5α‐spirostan‐3‐β‐yl‐ O ‐α‐l ‐rhamnopyranosyl‐(1 → 2)‐β‐d ‐galactopyranoside (1) and new saponin (25 R )‐1β, 2α‐dihydroxy‐5α‐spirostan‐3‐β‐yl‐ O ‐β‐d ‐galactopyranoside (2). While 2 showed little or no antifungal activity at the highest concentration tested, 1 inhibited growth of Saccharomyces cerevisiae (minimum inhibitory concentration (MIC) of 15–25 μM), Candida albicans, Cryptococcus neoformans, and Fusarium graminearum (MIC of 132–198 μM). Copyright © 2015 John Wiley & Sons, Ltd.